2018
DOI: 10.1186/s40729-017-0112-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of systemically or locally administered mesenchymal stem cells on tissue repair in a rat oral implantation model

Abstract: BackgroundMultipotent mesenchymal stem cells (MSCs) are used clinically in regenerative medicine. Our previous report showed systemically injected MSCs improved peri-implant sealing and accelerated tissue healing. However, the risks of systemic MSC administration, including lung embolism, must be considered; therefore, their local application must be assessed for clinical safety and efficacy. We investigated differences in treatment effect between local and systemic MSC application using a rat oral implantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…Regarding the effect of administration method, we previously conducted a study comparing systemic and topical administration, which suggested that subcutaneous administration of MSCs was ineffective when not applied with a scaffold [28]. Similar to previous findings [36,37], the lung and liver accumulated many cells from the systemic circulation.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Regarding the effect of administration method, we previously conducted a study comparing systemic and topical administration, which suggested that subcutaneous administration of MSCs was ineffective when not applied with a scaffold [28]. Similar to previous findings [36,37], the lung and liver accumulated many cells from the systemic circulation.…”
Section: Discussionsupporting
confidence: 68%
“…Both groups showed similar promotion of wound healing after tooth extraction, compared with both control groups ( Figure 5C). On the contrary, we recently reported that the high density of MSCs at the injected site following local administration meant that it was hard for them to move from the administration site to the site of inflammation [28].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, with all drug therapeutics, the mode of drug delivery and targeting strategy needs to be given serious consideration. Dependent on the indication, MSCs have been delivered via multiple routes of administration, from direct injection to IV delivery 83 . In the context of COVID-19-associated ARDS, MSCs need to exert their therapeutic effects in the lungs.…”
Section: Rationale For Msc Therapy To Manage Covid-19 Mediated Acute mentioning
confidence: 99%
“…To be classified as MSC, they must satisfy the minimum criteria set by the International Society for Cellular Therapy that they must be adherent to tissue culture treated plastic under ideal conditions and must be able to differentiate into adipocytes, chondroblasts and osteoblasts in-vitro (11). Although systemic administration of MSC carries a significant risk of pulmonary embolism and accumulation in healthy organs, Kanawaza et al found that it has a higher efficacy when compared to local administration (12).…”
Section: Introductionmentioning
confidence: 99%